Dinâmica espaço-temporal das frentes pioneiras no Estado do Pará - Marcelo Thalês; René Poccard-Chapuis (Confins)
Reducing deforestation in the Brazilian Amazon is the target of numerous public policies seeking to promote more sustainable forms of territorial development. Current monitoring systems provide excellent quantification of deforestation, though still inefficient in qualitative analysis part of the processes that lead to the removal of the forest in the region. Complex factors related to the expansion, intensification, diversification of economic activities, infrastructure and financing policies, forces of commodity markets promote distinct changes in Amazonian territories, determining the dynamics of deforestation in the pioneer fronts in the region. In this context, the objective of this research is to present a new methodology based on a systemic representation of pioneer fronts from the public data of deforestation. This methodology allows monitoring of agrarian transformations of pioneer fronts, providing useful information to decision-makers for a better adaptation of agricultural and environmental policies in the region. In this article, the methodology was applied in the State of Pará, where deforestation data were mapped into cells of 5x5 km, the dates 2000, 2005 and 2009, and linked to a typology, defined conceptually, which allowed to classify each cell in each date. Thus it was possible to locate the regions of pioneer fronts and characterize the dynamics of deforestation and land use types in these regions, in addition to qualifying processes observed over time. Thus, it was assessed that the methodology is adequate and that can be a tool of analysis for decision makers. However, we identified some methodological limitations, and highlight the importance of integrating other data sources to refine the approach.